Bachelor of Fine Arts Graduates of the College of Architecture and Fine Arts in Bulacan State University: An Employability Tracer Study of 2021, 2022, 2023 - Estacio, Dennis L.; Rivera, Vim Kiester C. (Future Science / FSH-PH Publications, 2025)
The employability of Bulacan State University's College of Architecture and Fine Arts Bachelor of Fine Arts (BFA) graduates, specifically those from the graduating classes of 2021, 2022, and 2023, is examined in this study. The study intends to assess alumni's current employment status, the relevance of their academic training to their professional roles, and the factors that influence their career paths and job satisfaction in light of the growing need to evaluate how well higher education programs prepare graduates for the workforce. Through follow-up interviews with a representative sample of graduates and structured online surveys, the researchers employed a descriptive study methodology to gather both quantitative and qualitative data.